Design Of Building Gear Motion Control Systems On Bicycles Using Voice Comments - ilham ramadhan putra; Putri Elfa Mas'udia; Hadiwiyatno Hadiwiyatno (Politeknik Negeri Malang, 2023)
Voice recognition is also connected to the microcontroller connected to the servo motor to move the derailleur rear as a gear drive. The results of research on the gear motion control system on bicycles using voice comments can move in the correct gear position. Storage of voice commands is done 7 times and repetition of the same command no later than 4 times while the fastest 2 times repetition. Test results in a crowded condition obtained 72% success and an average delay of 1.38 seconds and the test results in a quiet state obtained the success of 88% and an average delay of 1.20 seconds. The results of this study indicate that this study is able to move the gear in a moving state with voice commands in a quiet state, the maximum level of voice commands is 96.1 dB and the minimum level of voice commands is 80.2 dB when crowded, the maximum level of voice commands is 101.9 dB and obtained the minimum level of voice commands is 88.1 dB, but this research still has shortcomings, namely if the voice command given is above the maximum voice command level and below the minimum level, the voice command cannot be processed and the gear cannot move. seen from the difference between the maximum crowded state and the maximum quiet state of 5.8 dB and the difference between the minimum crowded state and the minimum quiet state of 7.9 dB.